Studies on the Impact of Seasons on Leaf Dust Accumulation and Biochemical Parameters of Selected Plant Species along Side the National Highway-7 in Sirmaur, H.P, India - Pandit, Jyotsana; Sood, Anil; Bhardwaj, Satish Kumar; Sharma, Anish Kumar (Modern Advances in Geography, Environment and Earth Sciences Vol. 3, 2021)
The present study was carried out to assess the dust interception efficiency and impact of seasons on biochemical parameters of plant species growing alongside National Highway (NH-7) at Sirmaur, H.P, India. Plants are universal sink of CO2. The plant species selected for the study were Ficus roxburghii, Mallotus philippensis, Shorea robusta, Woodfordia fruticosa. The observed trend of dust accumulation was in the order Ficus roxburghii (38.30 mg m-2) >Shorea robusta (26.94 mg m-2),>Mallotus philippensis (22.31 mg m-2) >Woodfordia fruticosa (16.70 mg m-2). The present study revealed, that the leaf dust accumulation decreased with increasing distance from the national highway. Leaf dust accumulation was influenced by the seasons of the year with the maximum (30.70) in pre-monsoon and the minimum (21.42) in post-monsoon season.